(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2021)
Current orthopedic plates come in standardized sizes using bio-compatible materials such as stainless steel and titanium. The toughness of the metallic materials and the standardizes sizes of the plates, however, are major causes for a delayed healing of the fracture. In the worst case, this effect can lead to a non-union of the bone. In this study, we employed 3D-printing to tailor the mechanical properties of the bone plates using four different lattice designs. The functionality of the semi porous implants was systematically evaluated under both of in vitro and in vivo animal studies. The results indicate that the novel implant design induces osteointegration suggesting an improved recovery of the fracture.